Great dialogues of Plato : complete texts of The republic, The apology, Crito, Phaedo, Ion, Meno, Symposium - Plato (Signet Classics, 2015)
A translation of the complete texts of "The Republic," "The Apology," "Crito," "Phaido," "Ion," "Meno," and "Symposium" reveals the genius of Plato as he struggled with education, justice, the "philosopher king," and utopian visions of society.